The Effect Of Work Motivation, Work Discipline, And Competence On Employee Performance At The Environmental Service Office Of Wonogiri Regency - Putri Nur Latifah; Sri Wijiastuti; Zandra Dwanita Widodo (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study was designed to determine how work motivation, work discipline, and competence affect employee performance at the Wonogiri Regency Environment Agency. In the context of bureaucratic reform, improving the performance of the civil service is a top priority so that public services can be more effective and accountable, especially in the field of the environment. Adopting a descriptive quantitative approach through a survey method, this study involved all employees of the Wonogiri Regency Environment Agency as the population, with 40 respondents selected using total sampling technique. Data were obtained through a closed questionnaire using a Likert scale from 1 to 5, then analyzed with multiple linear regression using SPSS software version 25. The findings reveal that work motivation, work discipline, and competence have a significant positive impact on employee performance, both collectively and individually. The adjusted coefficient of determination (Adjusted R²) value reached 0.635, meaning that 63.5% of the variation in employee performance can be explained by these three variables, while the rest is influenced by other factors outside the scope of the study. These results emphasize the urgency of human resource management that focuses on improving motivation, discipline, and competence to strengthen organizational performance in the public sector.